Tangsi-Tangsi Kolonial dan Tahanan Perempuan di Sumatera Barat - Dedi Arsa; Lukmanul Hakim (Kafa`ah: Journal of Gender Studies, 2019)
This article studies the women’s ward and the Dutch colonial regime to the female prisoners in West Sumatera. (Sumatra’s Westkust). As the historiography works it use a modern histories arrangements: heuristic, internal – external critics; Interpretation classification; explanation in historiography. It uses female history approach, studying the the womens’ position under the patriarchal. This study reveals that : The prisons had been built since 17th Century, it was began at Padang to the higher land as the Nederland Political Power became more powerfull; 2) It was recorded that was no women’s ward at that time, there was only a special room among the men’s for the women before they were sent to Java, all of the personels were males; 3) The inavailability of women’s ward and the female personels make the females prisoner  became more badly suffer as their punishment had been doublelized especially for those who were coomited to custom and moral.